Moral disorder : stories - Atwood, Margaret, 1939- (New York : Nan A. Talese, 2006)
A collection of short fiction presents ten stories that capture important moments in the course of a life and in the lives intertwined with it, in a volume that ranges from the 1930s to the 1980s.
The bad news -- The art of cooking and serving -- The headless horseman -- My last duchess -- The other place -- Monopoly -- Moral disorder -- The entities -- The labrador fiasco -- The boys at the lab.
Keywords: Autobiographical fiction, Canadian